Penentuan Umur Matahari Menggunakan Kesetaraan Massa dan Energi Einstein - Alfianri, Alfianri (el-Khuwailid: Journal of Multidisciplinary Studies, 2025)
The topic of luminosity in the solar system is inherently abstract, as it can only be visualized through illustrations or images. Understanding the solar system, with the sun as its center, is crucial for developing students’ scientific reasoning. Like all celestial bodies, the sun will eventually cease to exist, yet no technology currently allows for precise calculation of its remaining lifespan. This study investigates the remaining lifetime of the sun using Einstein’s mass-energy equivalence. This research aims to enhance the comprehension of high school students (SMA/MA) regarding the solar system’s mechanisms and to refine their ability to apply derived formulas, particularly in mass-energy equivalence. A descriptive method is used, drawing data from credible scientific journals. The current age of the sun is estimated at 4.5 billion years, determined by comparing the ages of the oldest terrestrial rocks and meteorites. The sun’s remaining lifetime is calculated using Einstein’s mass-energy equivalence equation, yielding 1.47 × 10¹³ years until it exhausts its mass through nuclear reactions.